FACES DA POESIA DE ASSIONARA SOUZA: MULHER, ESTÉTICA, CIBERESPAÇO - Pszdzimirski, Brunna (2021)
This study aims to analyze selected poems by Assionara Souza, published between the years 2014 and 2019 in different digital media. Having published four books of short stories and only one of poetry, it can be seen that the poet's preference is to publish her poems within cyberspace, using several platforms. Among them are her personal blog "Cecília não é um cachimbo", the collective blog "Escritoras suicídas" and her personal Facebook profile. In view of this, the main objective of this research is to analyze those selected poems considering how the poet's voice and speech present themselves in different facets of her poetry. In this way, the work is organized into three chapters that seek to establish which tools make this multiplicity possible in Assionara's poetics. Firstly, it seeks to contextualize the poet herself and the contemporary movement in which she participates. Thus, concepts from different theorists are used, including among them: Giorgio Agamben, (2002; 2007a; 2007b; 2008; 2009; 2014) and Susana Scramim (2007; 2016) that seek to elucidate what is the contemporary. At this moment, we seek to do a briefly contextualization of the written production done by women in Brazil and in Paraná and the relationship between this production and the publication of works in digital environments, checking which possible reason leads Assionara to publish in these spaces. There is also the analysis of “being a poet”, observing how the writer sees the function of the poem and the poet, and for this purpose, among the theoretical anchors, studies by Walter Benjamin (1987a, 1987b, 1987c) and Jacques Derrida (2001) are used. Secondly, as we delve into the lyrical of Assionara, it is seen how the contemporary poem can be multiple, unfoldable, plural. Thus, reflections arise covering the poem as an enigma, as a non-specific form. It is noticed that this poetics dialogues with different forms and means, such as cinema, works of art and political positions. To this end, the readings are based on the reflections of Florencia Garramuño (2014a; 2014b), Ana Kiffer (2014) and Josefina Ludmer (2010). Thirdly, and lastly, it is identified that this non-specificity, or expansiveness, brings to the poetry of Assionara voices of other poets and writers, becoming a space full of references, which change the meaning of her writing, as well as the structures of the poem. In this way it is possible to perceive affective and addressing issues in the construction of the lyric. For this moment, the analyzes come from the studies of Rita Lenira de Freitas Bittencourt (2013; 2016; 2017; 2020), Luciana Di Leone (2014) and Celia Pedrosa (2014; 2018).